2007
DOI: 10.1016/j.breast.2006.11.003
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of age and clinical factors on quality of life in early breast cancer: An analysis of 2208 women recruited to the UK START Trial (Standardisation of Breast Radiotherapy Trial)

Abstract: Summary Quality of life (QOL) assessments of women entering a UK randomised trial of adjuvant radiotherapy (START) were investigated to estimate the independent effects on QOL of age, time since surgery, type of breast surgery, chemotherapy and endocrine therapy. QOL was evaluated using the EORTC general cancer QOL scale (EORTC QLQ-C30), breast cancer module (BR23), the Body Image Scale (BIS) and the Hospital Anxiety and Depression Scale (HADS). Independent effects of age and clinical factors were tested using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

22
123
8
24

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 189 publications
(178 citation statements)
references
References 35 publications
(36 reference statements)
22
123
8
24
Order By: Relevance
“…This was followed by insomnia with 13.5% of participants scoring more than 66.7%. These results are close to regional and international figures (Hopwood et al, 2007;Waldmann et al, 2007;Jassim and Whitford, 2013). Studies examining the prevalence of fatigue among breast cancer patients found that up to 99% of patients suffer from some degree of fatigue during chemotherapy and/or radiotherapy and that more than 60% of them experience moderate to severe fatigue (Bower et al, 2000;2006).…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…This was followed by insomnia with 13.5% of participants scoring more than 66.7%. These results are close to regional and international figures (Hopwood et al, 2007;Waldmann et al, 2007;Jassim and Whitford, 2013). Studies examining the prevalence of fatigue among breast cancer patients found that up to 99% of patients suffer from some degree of fatigue during chemotherapy and/or radiotherapy and that more than 60% of them experience moderate to severe fatigue (Bower et al, 2000;2006).…”
Section: Discussionsupporting
confidence: 79%
“…This score is close to scores reported in Kuwait (Alawadi and Ohaeri, 2009), but slightly lower than scores reported in Bahrain (Jassim and Whitford, 2013) and Germany (Waldmann et al, 2007). The remaining scores of QLQ-C30 functional scales were also lower than those reported in Western countries (Hopwood et al, 2007;Waldmann et al, 2007). The physical functioning mean score in this study was 69.6±26.1 SD, which is lower than that reported in Bahrain (mean=74.9±21.7 SD) (Jassim and Whitford, 2013) and much lower than reported from Germany (mean=93.2±6.8 SD) (Waldmann et al, 2007).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations